2000
DOI: 10.1111/j.1553-2712.2000.tb02063.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Community Intervention to Reduce Patient Delay Time on Use of Reperfusion Therapy for Acute Myocardial Infarction Rapid Early Action for Coronary Treatment (REACT) Trial

Abstract: Abstract. Background: Reperfusion therapy for acute myocardial infarction (AMI) is a time-dependent intervention that can reduce infarct-related morbidity and mortality. Out-of-hospital patient delay from symptom onset until emergency department (ED) presentation may reduce the expected benefit of reperfusion therapy. Objective: To determine the impact of a community educational intervention to reduce patient delay time on the use of reperfusion therapy for AMI. Methods: This was a randomized, controlled commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…24,25 For patients at risk for ACS (and for their families), primary care physicians and other healthcare providers should consider discussing the appropriate use of aspirin and activation of EMS system. Furthermore, an awareness of the location of the nearest hospital that offers 24-hour emergency cardiovascular care can also be included in this discussion.…”
Section: Prehospital Management Patient and Healthcare Provider Recogmentioning
confidence: 99%
“…24,25 For patients at risk for ACS (and for their families), primary care physicians and other healthcare providers should consider discussing the appropriate use of aspirin and activation of EMS system. Furthermore, an awareness of the location of the nearest hospital that offers 24-hour emergency cardiovascular care can also be included in this discussion.…”
Section: Prehospital Management Patient and Healthcare Provider Recogmentioning
confidence: 99%
“…The primary REACT study population differed from that of the present study in that the present study focused only on patients who were admitted to the hospital and were subsequently found to have an acute MI. Hedges et al, 16 in a subset of the REACT study population with acute MI, reported that 40% were transported by EMS. Furthermore, these investigators observed that the rate of reperfusion therapy within 6 hours of symptom onset was significantly greater for acute MI patients when transported by EMS (36% versus 24%, PϽ0.0001).…”
Section: Prior Studiesmentioning
confidence: 99%
“…Furthermore, these investigators observed that the rate of reperfusion therapy within 6 hours of symptom onset was significantly greater for acute MI patients when transported by EMS (36% versus 24%, PϽ0.0001). 16 …”
Section: Prior Studiesmentioning
confidence: 99%
“…84,106 Deference toward physicians causes delays when symptoms occur during off hours. 90,107 Persons who call a physician are less likely to use EMS. 108 Patients who use EMS receive reperfusion therapy faster than those who do not.…”
Section: Social Cognitive and Emotional Factorsmentioning
confidence: 99%